Comparison of oncologic outcomes between elective partial and radical nephrectomy in patients with renal cell carcinoma in CT1B stadium - Marić, Predrag; Aleksić, Predrag; Košević, Branko; Jovanović, Mirko; Bančević, Vladimir; Simić, Dejan; Rančić, Nemanja (Vojnosanitetski pregled, 2022)
Background/Aim. In renal cell carcinoma (RCC), the choice of surgical technique, radical (RN) or partial nephrectomy (PN), is still center-dependent because there are still no absolute recommendations for this approach. The aim of this study was to analyze the oncological aspects, time until recurrent disease appears, and cancer-specific survival in patients with RCC in T1bN0М0 stadium depending on the type of surgical procedure, PN or RN technique. Methods. In a clinical observational study, data of 154 patients operated at the Clinic for Urology, Military Medical Academy, Belgrade, Serbia with a mean follow-up period of no less than five years were analyzed. Patients were divided into two groups; a group of patients with RN and a group of patients with PN. The inclusion criteria were: renal tumors 4–7 cm, histopathological confirmation of RCC, absence of metastasis, and normal serum creatinine. Exclusion criteria included: the presence of other malignancies, solitary functional kidney or comorbidities that can compromise renal function, bilateral tumors, or unilateral multiple tumors. Results. The study analyzed data from 154 patients, 97 (63%) RNs, and 57 (37%) patients that underwent PN. Analyzing cancer-specific survival in four patients with RN, there was a disease advancement that led to a lethal outcome, and one PN patient died as a result of local relapse and distant metastasis. Conclusion. Based on our results, PN is a good and safe treatment option for patients with RCC in T1b stadium. PN offers a similar tumor control and better cancer-specific survival.
Keywords: carcinoma, renal cell; kidney neoplasms; neoplasm metastasis; neoplasms staging; nephrectomy; urologic surgical procedures